Rapid Assays for Quantitating Cytokine Gene Expression Without Target Amplification - Gonzales, F.R.; Lois, A.; Sewell, T.; LaCerte, C.; Gaynor, B.; Garcia, E.; Jazdzewski, M.; Oliver, T.; Postor, I.; Trainor, D. (Combinatorial Chemistry & High Throughput Screening, 2003)
Many drug discovery efforts are focused on finding candidates that alter gene expression of the cytokines involved in inflammation, allergy, and cell-mediated immunity. Current methods used to evaluate gene expression such as northern blot and RT-PCR are laborious, time-consuming, expensive, and are not conducive to high throughput screening. High Performance Signal Amplification (HPSA™) gene expression assays quantitate mRNA targets directly from cell lysate samples using DNA probe hybridization and fluorescent signal amplification. The assay format eliminates the need for RNA purification prior to testing and does not involve target amplification. The 96 or 384-well microplate formats allow the method to be run manually, by a workstation approach, or with full automation. Cellular mRNA levels are quantitated relative to a standard curve comprised of highly purified in vitro RNA calibrators. The analytical sensitivity is in the low attomole (10 -18 mole) range. This technique was used to monitor the transcription patterns of mRNA encoding TNF-α, IL-1β, and Interferon-γ in human cell lines or primary PBMC treated with inducers such as PMA, ionomycin, and endotoxin. The specificity, precision and reproducibility of the assay are sufficient to provide a reliable screening system. The HPSA gene expression assay system offers a rapid and convenient alternative to more cumbersome, expensive methods.
Keywords: gene expression assay